Prevalence of hepatitis C virus in alcoholic patients: role of parenteral risk factors - Galperim,Bruno (2006)
BACKGROUND: The prevalence of hepatitis C virus (HCV) infection is elevated in alcoholic patients, but the risk factors are unclear. The role of parenteral risk factors are indeterminated in this population. AIMS: To determine the prevalence of hepatitis C virus infection in alcoholic patients admitted to a detoxification unit and to evaluate the presence of underlying parenteral risk factors. METHODS: A total of 114 consecutive unselected alcoholic patients admitted to a single chemical dependency unit during 14 month were included. Epidemiological data and history of parenteral risk factors for hepatitis C virus infection were obtained with a standardized questionnaire. Blood was collected for determination of aminotransferases and anti-hepatitis C virus antibodies (ELISA-3). Positive samples were confirmed by polymerase chain reaction and tested for genotype. RESULTS: Among the 114 alcoholics, 17 (15%) were anti-hepatitis C virus positive. Of these, 12 (71%) had detectable serum HCV-RNA by PCR. Genotype 1 was found in six cases and genotype 3 in five (one patient was undetermined). Forty-nine (43%) patients had elevated serum ALT and/or AST at baseline. The comparison between the 17 positive and the 97 negative patients showed significant differences in mean serum ALT levels (42 ± 41 IU/L vs. 22 ± 20 IU/L), rate of elevated ALT (65% vs. 34%), and presence of parenteral risk factors (94% vs. 10%). Comparison between alcoholic patients with and without elevated aminotransferases showed significant difference only in the rate of positive anti-hepatitis C virus antibodies (24% vs. 7%). Furthermore, among the 17 anti-hepatitis C virus positive patients, the rate of detectable HCV-RNA was significantly higher in the 12 with elevated aminotransferases versus the 5 with normal aminotransferases (92% vs. 20%). CONCLUSIONS: There was a high prevalence of anti-hepatitis C virus antibodies in alcoholics and the majority was confirmed by the presence of detectable HCV-RNA. Intravenous drug use was the main risk factor for hepatitis C virus infection in this population.